Comparative Analysis of Prospective Physics Teachers’ Learning Achievement in Terms of Cognitive Style (Field Dependent and Field Independent) - Ahmad Busyairi; Ahmad Harjono; Himawati Hikmawati; Muhammad Zuhdi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to determine the comparison of student achievement with field-dependent (FD) and field-independent (FI) cognitive styles. The method used in this research is a comparative descriptive method with a quantitative approach. The sample consisted of 30 prospective physics teacher students who were studying at the University of Mataram. Research data were taken using the Group Embedded Figure Test (GEFT) and documentation of the study result card (SRC). GEFT is used to determine cognitive style while documentation is used to determine the cumulative achievement index (CAI) of students. Based on the results of the t-test at the 95% confidence level (α = 0.05) with the degree of independence (dk =   2= 28), it shows that there are significant differences in learning achievement between FI and FD students. The average learning achievement of FI students (CAI = 3.15) tends to be better than that of FD students (CAI = 3.37).